1987
DOI: 10.1128/jvi.61.4.1125-1135.1987
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic cross-reactions among herpes simplex virus types 1 and 2, Epstein-Barr virus, and cytomegalovirus

Abstract: Polyvalent rabbit antisera against herpes simplex virus type 1 and 2 (HSV-1 and HSV-2), cytomegalovirus (CMV), and Epstein-Barr virus (EBV), monospecific antisera against affinity-purified HSV-2 glycoproteins gB and gG, and a panel of monoclonal antibodies against HSV and EBV proteins were used to analyze cross-reactive molecules in cells infected with the four herpesviruses. A combination of immunoprecipitation and Western blotting with these reagents was used to determine that all four viruses coded for a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 44 publications
1
34
0
1
Order By: Relevance
“…Monoclonal antibodies E1D1 and F-2-1 were gifts from L. Hutt-Fletcher (Louisana State University Health Sciences Center, Shreveport, La.) and recognize the gH/gL complex and gp42, respectively (1,44). A large-scale preparation of the E1D1 and the F-2-1 antibodies was made at the Northwestern University Monoclonal Antibody Facility.…”
Section: Methodsmentioning
confidence: 99%
“…Monoclonal antibodies E1D1 and F-2-1 were gifts from L. Hutt-Fletcher (Louisana State University Health Sciences Center, Shreveport, La.) and recognize the gH/gL complex and gp42, respectively (1,44). A large-scale preparation of the E1D1 and the F-2-1 antibodies was made at the Northwestern University Monoclonal Antibody Facility.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a strong human-antibody response, with both HCMV' and EBV' human sera, against the sequence TVDSMIALDI (positions 643 -652) is clearly evident; it has to be emphasized that that this major antibody-binding fragment is not included in the region covered by the set of peptides used in previous studies [29]. Several examples of monoclonal antibodies and animal sera recognizing HSV gB and the corresponding proteins of other herpes viruses have been described [20]. Cross-reactivity among herpes viruses has also been observed for human sera [25].…”
Section: Discussionmentioning
confidence: 98%
“…glycoprotein C: AD-1, antigenic domain-I of gp58.coproteins, namely the Epstein-Barr-virus (EBV) and herpessimplex-virus (HSV) glycoprotein B (gB), and varicella-herpes-zoster-virus (VHZV) glycoprotein 11, whose role in eliciting a host-immune response has been clearly shown [lo, 17-191. Since cross-reactions of antisera directed against these proteins have been described [20], this feature must be considered for a detailed analysis of HCMV gp58 antigenic properties. These studies are significant, since it has been recently shown that the majority of neutralizing activity in convalescent-human serum is directed against gCI [21], and the isolated complex is also able to induce both humoral and cellular-immune responses in human volunteers [22].In previous studies a HCMV gp58 linear antigenic site, recognized by neutralizing antibodies, has been identified near amino acid 616 by the use of recombinant gp58-fusion proteins.…”
mentioning
confidence: 99%
“…La recherche d'anticorps hétérophiles et d'anticorps spécifiques contre les antigènes du virus d'Epstein Barr est utile pour le diagnostic d'une infection aiguë surtout en présence d'un haut index de suspicion clinique [7]. Toutefois une possible réaction croisée avec la sérologie du CMV nécessite une interprétation avec précaution [8]. Chez notre malade, l'évolution temporelle de ces sérologies pouvait aider à discerner entre les deux virus.…”
Section: Discussionunclassified